Long term high frequency sediment observatory in an alpine catchment: The Arc‐Isère rivers, France. Issue 2 (10th February 2021) - Thollet, Fabien; Rousseau, Christophe; Camenen, Benoit; Boubkraoui, Stephane; Branger, Flora; Lauters, François; Némery, Julien
Abstract: We present a dataset on to the Arc‐Isère long‐term environmental research observatory, which is part of the Rhône Basin Long Term Environmental Research Observatory. This alpine catchment located in the French Alps is characterized by high Suspended Particulate Matter (SPM) in anthropogenized valleys. Suspended Sediment Concentrations (SSC) naturally observed in the river are very high, ranging from a few tens of milligrams per litre at low flow to tens of grams per litre during major natural hydrological events (floods, debris flows) or river dam hydraulic flushes. One research objective related to this site is to better understanding the SSC dynamics along the river using a system of nested catchments (Arvan, Arc, and Isère) in order to assess both temporal and spatial dynamics. The data allow the quantification of fine sediment yields and also the evaluation of possible morphological changes due to fine sediment deposition or resuspension. Additionally, the observatory database support studies on contaminants (either dissolved or particulate contaminants). Our monitoring includes six stations with high frequency (2–30 min) streamflow, SSC measurement using turbidity sensors, and associated automatic sampling. Discharge is measured via water level measurements and a rating curve. The oldest station (Grenoble‐campus) started recording discharge and concentration data from April 2006 while others stations were built between 2009 and 2011. Data are available in an online data website called 'Base de Données des Observatoires en Hydrologie' (Hydrological observatory database, https://bdoh.irstea.fr/ARC-ISERE/ ) with a DOI reference for the dataset. The hydrological and sediment transport time series are stored, managed and made available to a wide community with unfettered access in order to be used at their full extent. This database is used as a data exchange tool for both scientists and operational end‐users and there is an associated online tool to compute integrated fluxes. Abstract : Suspended Sediment Fluxes on Arc / Isère Observatory obtained with water discharge and turbidity measurements.